Development of a new design for cold energy storage using finned porous containers filled with nanomaterials - Mashhour A. Alazwari; Ali Basem; Hussein A.Z. AL-bonsrulah; Nidal H. Abu-Hamdeh; Awatif M.A. Elsiddieg; Abdulmalik A. Aljinaidi (Results in Engineering, 2025)
This study numerically investigates the freezing behavior in a finned container filled with water enhanced by hybrid nanoparticles to boost thermal conductivity. A novel combination of reduced porosity, hybrid nanofluids, and radiation modeling is applied to accelerate solidification. The equations are solved implementing an implicit scheme with adaptive meshing for improved accuracy. Results show that reducing porosity enhances the solid fraction and shortens freezing time by 80.6 %. The addition of hybrid nanoparticles leads to a 6.6 % reduction, while radiation further decreases solidification time by 14.23 %. These findings demonstrate the synergistic potential of combining thermal enhancement techniques for efficient cold energy storage.